Gleaning evolutionary insights from the genome sequence of a probiotic yeast Saccharomyces boulardii - Khatri, Indu (BioMed Central, 2013)
BACKGROUND: The yeast Saccharomyces boulardii is used worldwide as a probiotic to alleviate the effects of several gastrointestinal diseases and control antibiotics-associated diarrhea. While many studies report the probiotic effects of S. boulardii, no genome information for this yeast is currently available in the public domain. RESULTS: We report the 11.4 Mbp draft genome of this probiotic yeast. The draft genome was obtained by assembling Roche 454 FLX + shotgun data into 194 contigs with an N50 of 251 Kbp. We compare our draft genome with all other Saccharomyces cerevisiae genomes. CONCLUSIONS: Our analysis confirms the close similarity of S. boulardii to S. cerevisiae strains and provides a framework to understand the probiotic effects of this yeast, which exhibits unique physiological and metabolic properties.